Complementary bidding and cartel detection: Evidence from Nordic asphalt markets - Aapo Aaltio; Riku Buri; Antto Jokelainen; Johan Lundberg (Helsinki Graduate School of Economics, 2023)
A key challenge in cartel enforcement is identifying collusive agreements. We study two major Nordic procurement cartels that operated in the asphalt paving market. We find evidence that during the cartel period bids were clustered and the winning bid was isolated. We implement two cartel detection methods that exploit variation in the distribution of bids. The method developed by Clark et al. (2020) correctly rejects competitive bidding for the cartel period in both markets. The method suggested by Huber and Imhof (2019) predicts a significantly higher probability of collusion for the cartel period in one of the markets. Our results indicate that statistical screening methods with modest data requirements can be useful for competition authorities in detecting collusive agreements.
Keywords: L22; L74; D44; H57; 330; procurement; bidding ring; collusion; antitrust; complementary bidding; detection